Notifiche
Cancella tutti

Integrale definito

  

1
153

Risolvere senza la tecnica X sostituzione.

Autore
1 Risposta



2

∫((x^2 + 3·x + 1)·e^(1 - x)) dx =

=e·∫(e^(-x)·(x^2 + 3·x + 1)) dx =

=e·(∫(x^2·e^(-x)) dx + ∫(3·x·e^(-x)) dx + ∫(e^(-x)) dx=

=e·(- x^2·e^(-x) + 2·∫(x·e^(-x)) dx + ∫(3·x·e^(-x)) dx + ∫(e^(-x)) dx =

=e·(- x^2·e^(-x) + 2·(- x·e^(-x) + ∫(e^(-x)) dx + ∫(3·x·e^(-x)) dx + ∫(e^(-x)) dx=

=e·(- x^2·e^(-x) + 2·(- x·e^(-x) - e^(-x)) + ∫(3·x·e^(-x)) dx + ∫(e^(-x))dx =

=e·(- (x^2 + 2·x + 2)·e^(-x) + 3·∫(x·e^(-x))dx + ∫(e^(-x)) dx =

=e·(- (x^2 + 2·x + 2)·e^(-x) + 3·(- x·e^(-x) + ∫(e^(-x)) dx + ∫(e^(-x)) dx =

=e·(- (x^2 + 2·x + 2)·e^(-x) + 3·(- x·e^(-x) - e^(-x)) + ∫(e^(-x)) dx =

=e·(- (x^2 + 5·x + 5)·e^(-x) - e^(-x))=

=- e^(1 - x)·(x^2 + 5·x + 6)

Valutato in x = 1

- e^(1 - 1)·(1^2 + 5·1 + 6) = -12

Valutato in x = -2

- e^(1 - (-2))·((-2)^2 + 5·(-2) + 6) = 0

Risultato: -12

@lucianop Grande Luciano, grazie mille.

@alby

Di nulla. Ciao.



Risposta
SOS Matematica

4.6
SCARICA